Musician Problem: Internal and External Aspects - Jatmika, Ovan Bagus (Journal of Music Science, Technology, and Industry, 2020)
Purpose: This paper explores various problems faced by music players in general and the solutions about the problems. Research methods: These problems are categorized into two, namely internal and external. Internal problems are related to technical and psychological problems, while external problems are related to communication capacity. Results and discussion: Internal problems can be experienced by all music players without considering the kind of their performances (solo or ensemble), external problems specifically only appear in the ensemble. The solution to the technical problems is trying to understand the score from the broadest possible perspective (accommodating at least three things: assumptions about the style of music, the intention of the composer, and the role of the player in interpreting the work) so that the player can construct sound imaginations without being overshadowed by technical constraints. Implication: Psychological problems can be mitigated by many things, but the most recommended method is cognitive behavior therapy, where musicians are taught to always bring positive thoughts in any situations